Effect of Preparation Acetone on Fish Bones Synthesized Through Sintering Method to Improve Hydroxyapatite Characteristics - Kusumawardani, Ratna; Noviyanti, Atiek Rostika; Nurhadi, Mukhamad; Umar, Akrajas Ali (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
In the development of advanced materials and various technological applications, the preparation and sintering processes have become two important factors in determining material characteristics. This research focuses on two main aspects, namely the effect of fish bone preparation by soaking in acetone and the surface area of the material in the sintering process as part of the process of developing better materials. This research aims to determine the effect of soaking fish bone powder with acetone and the effect of the surface area of sintered fish bones to produce hydroxyapatite (HA). The immersion process with acetone is included in the sample preparation stage, while the sintering process is included in the material synthesis stage. These two things can affect the characteristics of the HA produced after analysis from the X-ray diffraction test. The HA structure obtained from all samples is hexagonal with cell parameter values a = b ≠ c and space group P 63 / m, where all samples have a value range of a = b = 9,42 Å and c = 6,88 Å. HA crystallinity was identified through the XRD peak at 2θ = 25,8 (002); 31,7 (211); 32,1 (112); 32,8 (300); 34,0 (202); 39,7 (310); 46,6 (222); 49,4 (213); 50,4 (321). The PAF-900 and CAF-900 samples are similar to HA in JCPDS 01-089-4405 whose compound formula is Ca5(PO4)3(OH) while the PWAF-900 sample is similar to HA in JCPDS 01-075-3727 whose compound formula is Ca5(PO4)3(CO3)0.01(OH)1.3. The percentage of crystallinity of PAF-900, CAF-900, and PWAF-900 respectively was 84,767; 73,506; and 71,962% with HA grain sizes of 0,8964; 0,6808, and 0,7398 nm. The HA density of PAF-900 and CAF-900 samples is 3,149 g/cm3 while PWAF-900 is 3,146 g/cm3. Based on this description, it can be concluded that the soaking preparation stage with acetone produces HA with the chemical formula Ca5(PO4)3OH with a higher percentage of crystallization and is denser compared to HA obtained without going through the soaking preparation stage with acetone. The sintering stage also plays an important role in increasing the crystallization percentage. The surface area of the material being sintered also influences the percentage of crystallization and the grain size of the resulting HA. Sintered fish bone powder produces a greater percentage of crystallization and grain size than fish bone chunks